Spatial distribution of LTi-like cells in intestinal mucosa regulates type 3 innate immunity - Sécca, Cristiane (Proc Natl Acad Sci U S A, 2021)
Lymphoid tissue inducer (LTi)-like cells are tissue resident innate lymphocytes that rapidly secrete cytokines that promote gut epithelial integrity and protect against extracellular bacterial infections.Here, we report that the retention of LTi-like cells in conventional solitary intestinal lymphoid tissue (SILT) is essential for controlling LTi-like cell function and is maintained by expression of the chemokine receptor CXCR5. Deletion of Cxcr5 functionally unleashed LTi-like cells in a cell intrinsic manner, leading to uncontrolled IL-17 and IL-22 production. The elevated production of IL-22 in Cxcr5-deficient mice improved gut barrier integrity and protected mice during infection with the opportunistic pathogen Clostridium difficile. Interestingly, Cxcr5(−/−) mice developed LTi-like cell aggregates that were displaced from their typical niche at the intestinal crypt, and LTi-like cell hyperresponsiveness was associated with the local formation of this unconventional SILT. Thus, LTi-like cell positioning within mucosa controls their activity via niche-specific signals that temper cytokine production during homeostasis.